Farmers' perception on usefulness of ICT initiatives in Agriculture - P.Gidda Reddy,; P.Punna Rao,; M.Mallika,; I.Aruna Sri, (Journal of Agricultural Extension Management, 2025)
A study was conducted to determine the perception of farmers on the usefulness of ICT initiatives for farming. Farmer beneficiaries of JCT initiatives namely, aAQUA, e-choupal, V-Agri, V-Aqua, e-Sagu and Farmers Call Centre (FCC) covering Maharashtra, Madhya Pradesh and Andhra Pradesh were interviewed. The results of the study revealed that the initiatives were moderately useful for farmers for obtaining agriculture and related information for their farms. Though, the queries of farmers were addressed as required, the expectations of the farmers are high and hence the utility and performance of the JCT initiatives need to be improved..